Patients with humoral primary immunodeficiency do not develop protective anti-influenza antibody titers after vaccination with trivalent subunit influenza vaccine - van Assen, Sander (Clinical immunology (Orlando, Fla.), 2010)
Yearly influenza vaccination is recommended for patients with humoral primary immunodeficiency (hPID). However, humoral responses following vaccination can be expected to be reduced in these patients. The efficacy of influenza vaccination in patients with hPID, anti-influenza antibody responses was assessed in 26 patients with hPID and 26 matched healthy controls (HC) using hemagglutination inhibition assay. Following vaccination, geometric mean titers (GMT) significantly increased for all influenza strains in the HC group, but only for A/H1N1 in the patient group. Fold increase in anti-influenza titer and seroprotection rates were lower for patients than for HC for A/H3N2 and A/H1N1, leading to postvaccination titer > or =40 in only 29% and 83% vs. 77% and 100%, respectively. Previous vaccination in patients and treatment with IVIg did not result in a higher rate of postvaccination titer > or =40. In conclusion, patients with hPID show hardly any humoral response following influenza vaccination